Addressing treatment and care needs of older adults living with HIV who use drugs. Issue 8 (26th August 2020) - Chayama, Koharu Loulou; Ng, Cara; McNeil, Ryan
Abstract: Introduction: Older adults living with HIV (OALHIV; ≥50 years) who use drugs face unique needs and challenges that compromise their health and wellbeing due to the structural and environmental barriers they experience, in addition to being disproportionately affected by comorbidities. Nevertheless, research on this population is limited and work is needed to tailor and optimize their care and services. The purpose of this commentary is to address the key research gaps pertaining to OALHIV who use drugs. Discussion: We identified four key research gaps specific to OALHIV who use drugs. Gap 1: Increased understanding of how older adults manage HIV alongside comorbidities in the context of substance use is critical to optimize their care management. Gap 2: More information on the geriatric characteristics of OALHIV who use drugs and the need and role of harm reduction in geriatric care is necessary for the provision of appropriate and effective care. Gap 3: Greater knowledge around the adoption of harm reduction and case manager approaches in various care facilities is essential to ensure equitable access to care for OALHIV who use drugs. Gap 4: Improved understanding of barriers to high‐quality palliative care among OALHIV who use drugs is important to enhance quality of life across their life course. Conclusions: Addressing the identified gaps in literature will lead to a more fulsome understanding of the issues encountered by OALHIV who use drugs and inform the development and implementation of strategies that address disparities at the intersection of HIV, substance use and ageing.